A MSK Radiologist's Early Experience as a Department Chair: Climbing the Horizontal Ladder - Casagranda, Bethany U. (Seminars in Musculoskeletal Radiology, 2018)
A radiologist's training is designed to produce a professional with excellent interpretation skills. However, in today's health care environment, a successful radiologist may not be a successful leader or the opposite may be true. Leadership requires a different set of skills with knowledge of common concepts across all levels of health care delivery. When asked to take on administrative responsibilities, you anticipate constant work with occasional glory, but you may not realize the ladder of success is actually horizontal and the spotlight quite bright.In this personal narrative, I have illustrated my pathway to the chair position in the context of climbing the career ladder and entering the stage of leadership. I discuss common concerns facing radiology today and how we can all use our experience and leadership skills to overcome these challenges with effective solutions.
Keywords: radiology; leadership; burnout; institute; performance